2015
DOI: 10.1080/10986065.2015.1016819
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parent Literacy and Numeracy Expectations and Activities in Predicting Early Numeracy Skills

Abstract: The home numeracy environment (i.e., parents' numeracy expectations and activities), is related to early numeracy in young children. As recent studies have shown that both cognitive and linguistic factors play an important role in predicting numeracy development, it may be assumed that rather than the home numeracy environment, the home literacy environment predicts early numeracy. The present study examined this hypothesis by focusing on the specificity of the home numeracy environment. In a sample of 60 kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 55 publications
4
54
0
6
Order By: Relevance
“…Therefore, it is unlikely that the absence of the relation between the two methods is due to low validity or reliability. Additionally, the children's age in our study was comparable with previous home numeracy studies (e.g., Benavides‐Varela et al ., ; Segers et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is unlikely that the absence of the relation between the two methods is due to low validity or reliability. Additionally, the children's age in our study was comparable with previous home numeracy studies (e.g., Benavides‐Varela et al ., ; Segers et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This distinction between formal and informal home numeracy activities has further resulted in inconsistent findings. Some studies also showed that formal home numeracy activities were positively related to children's basic numerical skills (LeFevre, Polyzoi, Skwarchuk, Fast, & Sowinski, 2010;Segers, Kleemans, & Verhoeven, 2015). Others reported that a total score including both formal and informal activities was not related to children's basic numerical and calculation skills (Blevins-Knabe, Austin, Musun, Eddy, & Jones, 2000;Missall, Hojnoski, Caskie, & Repasky, 2015).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Further work would be needed to identify what mediates these specific associations. For example the presence of books in the house may mediate associations with English (Evans, Kelley, & Sikora, 2014;Sikora, Evans, & Kelley, 2018), while parents' numeracy may mediate associations with maths (Segers, Kleemans, & Verhoeven, 2015). Subject interest has been shown to interact with SES in predicting science attainment at age 15 across 57 countries (Drob, Cheung, & Briley, 2014) and it is also possible that specific subject interest plays an increasing role in attainment in other subjects over adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Home environment and early numeracy development Home numeracy environment involves both parents' practices (e.g., the amount and types of learning resources they provide children with and the frequency and nature of learning activities they engage children in) as well as attitudes (e.g., their perceptions of the importance of early numeracy learning; Anders et al, 2012;Blevins-Knabe, 2016;Segers, Kleemans, & Verhoeven, 2015). In the recent two decades, there has been growing interest in the role of home environment in early numeracy development among researchers.…”
Section: Statement Of Contributionmentioning
confidence: 99%